COMPARATIVE STUDY OF ARTICLES ON DIFFERENT SURGICAL APPROACHES BY DIVERSE AUTHORS IN TREATMENT OF CUBITAL TUNNEL SYNDORME - DZonov, Boro; Srbov, Blagoja (Македонско Лекарско Друштво - Macedonian Medical Association/De Gruyter, 2019)
Introduction. Cubital tunnel syndrome is the second most common compressive neuropathy in the upper limb. The diagnosis of cubital tunnel syndrome is primarily clinical. A thorough history should include the onset of symptoms, presence of grip or pinch weakness, numbness and the chronicity of the condition. Methods. Depending on symptoms and clinical signs, the surgical methods of choice include in situ open decompression, submuscular transposition, intramuscular transposition, subcutaneous transposition and medial epicondylectomy. APubMed search was conducted and published articles were comparedusing predetermined criteria. Data collected showed the follow-up of patients’ surgical treatment with different surgical approaches. The percentage results are shown as combined good and excellent outcomes. Results. Despite the different scoring scales used and difficulty comparing studies directly, the bulk of single technique outcomes studies and multi-technique comparative studies demonstrate that all surgical techniques discussed are effective treatment methods for cubital tunnel syndrome, but fail to demonstrate one technique to be uniformly superior to another. Conclusion. The literature, articles and casereports, state that all of the techniques are generally effective. Comparative studies show no statistical difference in outcomes with any presentedtechnique. One conclusion is obvious that transposition should be performed only when subluxation of the nerve is present. In conclusion, there is no superior technique and no gold standard in treatment ofcubital tunnel syndrome.
Keywords: cubital tunnel; ulnar nerve; decompression; transposition; ulnar neuropathy